Satisfaction With Life, Coping, and Spirituality Among Urban Families. (October 2015) - Doolittle, Benjamin; Courtney, Malachi; Jasien, Joan
Background: Urban families face many challenges that affect life satisfaction, including low income, limited access to resources, and unstable neighborhoods.Purpose: To investigate life satisfaction and identify potential mediators: neighborhood stability, emotional coping strategies, religion, and spirituality.Methods: A convenience sample of families presenting to an urban primary care clinic for routine care filled out an anonymous, voluntary survey that included demographic data, the Satisfaction with Life Scale (SWLS), the Spiritual Inventory and Beliefs Scale, and an emotional coping inventory.Results: 127 individuals filled out the survey. Life satisfaction was high (21.3 ± 9). Families in the lowest quartile of the SWLS were 4.5 times as likely to have a child with a chronic medical illness. SWLS correlated with strategy planning ( r = 0.24, P < .01), external practices of religion ( r = 0.23, P < .01), and humility ( r = 0.18, P < .05).Conclusions: Encouraging patients' involvement in religion and certain coping strategies, especially among those families coping with children with special health care needs, may improve life satisfaction.